Feto-Maternal outcomes in Intrahepatic Cholestasis in Pregnancy in a Tertiary Care Centre in Eastern Nepal - Pokhrel Ghimire, Sita; Ghimire, Ashima; Jha, Gauri Shankar; Chhetry, Manisha; Kumar, Mahanand (Journal of Nobel Medical College, 2016)
Background Intrahepatic cholestasis of pregnancy has poor feto-maternal outcomes. To date there has been sparse publications regarding impact of intrahepatic cholestasis in feto-maternal outcomes in our setting. Therefore, we aimed to study the feto-maternal outcome in patients with intrahepatic cholestasis of pregnancy.Material and Methods A hospital based prospective cross-sectional study carried out in department of Obstetrics and Gynecology of Nobel Medical College, Biratnagar, Nepal from 1st January 2014 to 30th December 2015 in women who presented with pruritus in third trimester of pregnancy and having deranged liver function tests. All the cases were followed from admission to discharge. Socio-demographic, clinico-laboratory profile and feto-maternal outcomes were recorded in a preformed structured proforma. Descriptive statistics was used to present the data.Results Among 6,780 women admitted for delivery, 80 had cholestasis of pregnancy with incidence of 1.15%. 83% were of 18-35 years and 65% were primigravida. Most distressing symptom was generalized pruritus (75.0 %). The cesarean delivery rate was 46.25% and labor induction rate was (47.5%). Fetal complications were seen in majority of cases that included meconium aspiration syndrome 26 (32.5%), intrapartum fetal distress 21 (26.25%) and requirement of: intensive care 38 (48.75%). There were 7 perinatal and 3 neonatal deaths.Conclusion Intrahepatic cholestasis of pregnancy seems fairly common among pregnant women. It may be responsible for a large number of perinatal and neonatal deaths especially after 36 weeks of gestation. A large prospective study is needed to address the problems in time.Journal of Nobel Medical College Volume 5, Number 1, Issue 8, January-July 2016, 20-25